SEMIOTIC DESIGN - Tri Rahayu (Universitas Trisakti, 2009)
AbstractDesign Semiotics.Self-maturing linguistics itself, on the the contextual-communication as case of keywords of the problem becomes such general symptoms towards the ultimate point where everything is a 'language' . On the most significant relation about discourses of design as linguistics phenomenon 'first and foremsot' on the viusal culture framework as formed by contemporary civilizationis felt to position 'design' as a centre of this civilization. Design become an intelegent zone expresses, the complexity needs and exixtential to outside-inside, is moving to the rotation of interiority inner -sublime of human. There, design becomes in nutrition of inner-human, expressing hidden experiences that is a confusion and 'beyond the wods, moreever to sophisticated epistemology, 'semiotics' here becomes a very important part of the expression of reality. This writing is trying to explore the semiotics framework on design. Abstrak.Design Semiotics.